A protocol-independent technique for eliminating redundant network traffic. - Spring, Neil T.
We present a technique for identifying repetitive information transfers and use it to analyze the redundancy of network traffic. Our insight is that dynamic content, streaming media and other traffic that is not caught by today's Web caches is nonetheless likely to derive from similar information. We have therefore adapted similarity detection techniques to the problem of designing a system to eliminate redundant transfers. We identify repeated byte ranges between packets to avoid retransmitting the redundant data.We find a high level of redundancy and are able to detect repetition that Web proxy caches are not. In our traces, after Web proxy caching has been applied, an additional 39% of the original volume of Web traffic is found to be redundant. Moreover, because our technique makes no assumptions about HTTP protocol syntax or caching semantics, it provides immediate benefits for other types of content, such as streaming media, FTP traffic, news and mail.
Keywords: Computer systems organization; Computer communication networks; Information systems; Information storage and retrieval; Online information services; Web based services; Algorithms; Design; Documentation; Management; Measurement; Performance; Standardization; Theory